Respon Pertumbuhan Planlet Anggrek Dendrobium sp. Melalui Aplikasi Ekstrak Tauge dan Air Kelapa pada Media Organik - HESTIN YUSWANTI; IDA AYU PUTRI DARMAWATI (Agrotrop : Journal on Agriculture Science, 2013)
The Growth Response of Orchid Plantlets of Dendrobium sp. by Aplicación of Bean Sprouts Extract and Coconut Water in Organic Medium The aim of this researh is to obtain the effect of coconut water and bean sprouts extract and the best combination added to organic medium on growth of orchid planlets in vitro. The experiment was conducted at Tissue Culture Laboratory of Agriculture Faculty, Udayana University, Pegok Denpasar from Mei until Oktober 2012. The research design was Completely Randomized Design (RAL) with ten treatments and six replications. The results of this ezperiment showed that addition of coconut water at concentration of 150 ml/l and bean sprouts extract of 50 ml/l resulted in the best growth of orchid planlet which includes the height of plantlets (4,10 cm), the number of leaf (3,33 leaves), length of root (1,07 cm). The total fresh weight of plantlet was 0,20 g and total oven dry-weight of plantlet was 0,021 g.